Pharmacokinetics and bioequivalence of two imidocarb formulations in cattle after subcutaneous injection - Wang, Honglei; Chen, Chen; Liu, Maolin; Chen, Xiaojie; Liu, Chunshuang; Feng, Yanyan; Yan, Xinbo; Liu, Yiming; Li, Xiubo (PLOS ONE, 2022)
Imidocarb (IMD) is commonly used for treatment of eperythrozoon, babesia, piroplasma and trypanosoma in animals, but there are few studies on its pharmacokinetics in cattle. The purpose of this study was to obtain pharmacokinetic parameters and assess the bioequivalence of subcutaneous injections of two IMD formulations in cattle. Forty-eight healthy cattle, 24 males and 24 females, were randomLy divided into two groups (test group and reference group) with 12 males and 12 females per group. The generic IMD was injected subcutaneously with a single dose of 3.0 mg/kg in the test group. Reference group animals were given one injection of the marketed IMD at the same dosage. The limit of detection (LOD) and limit of quantification (LOQ) for IMD in cattle plasma were 0.05 ng/mL and 0.1 ng/mL, respectively. The recoveries ranged from 88.50% to 92.42%, and the equation of this calibration curve was Y = 13672.1X+187.43. The pharmacokinetics parameters of the test group showed that the maximum concentration of 2257.5±273.62 ng/mL was obtained at 2.14±0.67 h, AUC0-t 14553.95±1946.85 ng·h/mL, AUC∞ 15077.88±1952.19 ng·h/mL, T1/2 31.77±25.75 h, CL/F 0.14±0.02 mL/h/g, and Vz/F 6.53±5.34 mL/g. There was no significant difference in AUC0-t, AUC∞ and Cmax between the test group and the reference group (P>0.05). The 90% confidence interval of AUC0-t, AUC0-∞ and Cmax in the test group was included in 80%–125% AUC0-t, AUC0-∞ and 70%–143% Cmax in the reference group, respectively. Based on these results, the two preparations were found to be bioequivalent.